RESTORATIVE JUSTICE DAN PROSPEK KEBIJAKAN IDEALNYA DALAM HUKUM PIDANA INDONESIA - Tongat Tongat (Faculty of Law, Universitas Diponegoro, 2013)
Crime prevention through the means of criminal law with the conventional characteristics expensive, unjust, immoral and failure continues to be a central issue of criminal law. Criminal law is also constantly criticized for its negative impacts such as stigmatization, dehumanization and prisonization which tend to be crimi:10genic. State's failure to meet